Recent and Emerging Advances in Spinal Deformity. Issue 3 (21st February 2017) - Smith, Justin S.; Shaffrey, Christopher I.; Bess, Shay; Shamji, Mohammed F.; Brodke, Darrel; Lenke, Lawrence G.; Fehlings, Michael G.; Lafage, Virginie; Schwab, Frank; Vaccaro, Alexander R.; Ames, Christopher P.
Abstract: BACKGROUND: Over the last several decades, significant advances have occurred in the assessment and management of spinal deformity. OBJECTIVE: The primary focus of this narrative review is on recent advances in adult thoracic, thoracolumbar, and lumbar deformities, with additional discussions of advances in cervical deformity and pediatric deformity. METHODS: A review of recent literature was conducted. RESULTS: Advances in adult thoracic, thoracolumbar, and lumbar deformities reviewed include the growing applications of stereoradiography, development of new radiographic measures and improved understanding of radiographic alignment objectives, increasingly sophisticated tools for radiographic analysis, strategies to reduce the occurrence of common complications, and advances in minimally invasive techniques. In addition, discussion is provided on the rapidly advancing applications of predictive analytics and outcomes assessments that are intended to improve the ability to predict risk and outcomes. Advances in the rapidly evolving field of cervical deformity focus on better understanding of how cervical alignment is impacted by thoracolumbar regional alignment and global alignment and how this can affect surgical planning. Discussion is also provided on initial progress toward development of a comprehensive cervical deformity classification system. Pediatric deformity assessment has been substantially improved with low radiation-based 3-D imaging, and promising clinical outcomes data are beginning to emerge on the use of growth-friendly implants. CONCLUSION: It is ultimately through the reviewed and other recent and ongoing advances that care for patients with spinal deformity will continue to evolve, enabling better informed treatment decisions, more meaningful patient counseling, reduced complications, and achievement of desired clinical outcomes.